Globalization and Local Profiles of Economic Growth and Industrial Change - Wolfgang Dauth; Jens Südekum (Institute for the Study of Labor (IZA), 2014)
We analyze how globalization has affected the sectoral anatomy of regional growth in Germany over the period 1978-2008. The aggregate German economy is characterized by a secular decline of manufacturing and a rise of modern service industries. This trend also known as Petty's law is not uniform across space, however. Some regions exhibit it at an even accelerated pace, while other regions have reinforced their manufacturing specializations. We first categorize all German regions into one of three groups, with "protrend", "anti-trend" or "featureless" growth. Afterwards we propose an explanation why a particular region ended up in one of those groups: We argue that the regional profiles of growth and change are systematically related to the initial sizes, and the import and export exposures of the local manufacturing sectors.
Keywords: R11; O14; F16; 330; structural change; local industry compositions; trade exposure; local employment growth